2005
DOI: 10.1111/j.1745-4530.2005.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Brandy Production by Batch Column Distillation With Reflux

Abstract: The relationship between the operating parameters of batch fruit spirits column stills with reflux and the congener (trace compounds that provide flavors and aromas) concentrations in resulting fruit spirits has not been widely studied. Congener concentrations were determined in three different collection fractions, or “cuts,” during batch distillation. Acetaldehyde and ethyl acetate were found in higher concentrations in the head cut, first overhead fraction, of the distillation and have lower boiling points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 7 publications
(15 reference statements)
8
43
0
Order By: Relevance
“…When distilling mixture has higher concentration of alcohol (higher than 40% (v/v) [44]), higher alcohol will distill following the boiling points, and their concentration will increase as the distillation process progresses. This explains why distillates in the column showed higher concentration of higher alcohol in the tail [21] and distillates in pot still (Figure 6) showed higher concentration of higher alcohol in the head [18,40].…”
Section: Distillation -Innovative Applications and Modelingmentioning
confidence: 66%
See 4 more Smart Citations
“…When distilling mixture has higher concentration of alcohol (higher than 40% (v/v) [44]), higher alcohol will distill following the boiling points, and their concentration will increase as the distillation process progresses. This explains why distillates in the column showed higher concentration of higher alcohol in the tail [21] and distillates in pot still (Figure 6) showed higher concentration of higher alcohol in the head [18,40].…”
Section: Distillation -Innovative Applications and Modelingmentioning
confidence: 66%
“…It appears mainly in the head fractions when distillation column was used [21]. Results of Cortes et al [32] showed the concentration of the methanol was seven times higher in the case of industrial distillation (means higher concentrates and cleanses of ethanol) than the concentration of methanol in the distillates obtained by simple pot still.…”
Section: Distillation -Innovative Applications and Modelingmentioning
confidence: 93%
See 3 more Smart Citations